Crocin ameliorates depressive-like behaviors induced by chronic restraint stress via the NAMPT-NAD+-SIRT1 pathway in mice. (July 2022) - Zhang, Feng; Zhu, Xinying; Yu, Ping; Sheng, Tingna; Wang, Yuqing; Ye, Yilu
Abstract: Aim: To investigate the effects of crocin on depression induced by chronic restraint stress (CRS) in mice. Methods: Depression model was established induced by CRS. All mice were divided into 4 groups randomly: normal group, model group, sertraline group and crocin group. From the 28th day after treatment, serials behaviors were conducted to evaluate the effects of crocin, including sucrose preference test (SPT), tail suspension test (TST), forced swimming test (FST), open field test (OFT), novel objective recognition test (NORT), social interaction test (SIT), and dominance tube test (DTT). Contents of Nicotinamide phosphoribosyltransferase (NAMPT), BDNF, CREB, pCREB and SIRT1 in prefrontal cortex (PFC) were detected by WB. The levels of CORT, DA, 5-HT, NE and NAD + in PFC were also detected by ELISA. Results: The results showed that crocin ameliorated the depressive-like behaviors, which manifested by increased sucrose consumption ratio and decreased immobility time in FST and TST. Crocin also increased the exploration time and exploration number in T2 phase in NORT, social preference index and social novelty index in SIT, reduced the defensive behavior in DTT. The results of WB showed crocin reversed the decreased contents of NAMPT, SIRT1, BDNF and pCREB/CREB in PFC induced by CRS. Additionally, crocin decreased the expression of cortisol (CORT) and increased the contents of DA, 5-HT, NAD +, but had no effects on NE between groups in PFC. Conclusion: In view of the findings, crocin ameliorates depression in mice, which may be associated with regulating NAMPT-NAD + -SIRT1 pathway. Highlights: Chronic restraint stress (CRS) induces depressive-like behaviors in mice. Exposure to CRS increases corticosterone level and decreases the expression of DA, 5-HT in PFC, but have no effect on NE. The contents of NAMPT, SIRT1, NAD+, pCREB/CREB and BDNF in PFC decreased significantly in CRS mice. Crocin regulates NAMPT-NAD + -SIRT1 signaling pathway. Crocin improves anxiety, depressive-like behaviors and cognitive function.